Knowledge, Attitudes and Practices on the Use of Botanical Medicines in a Rural Caribbean Territory - Vujicic, Tatijana; Cohall, Damian (Frontiers in Pharmacology, 2021)
The worldwide use of medicinal plant products has been steadily increasing over the past few decades, whereas the traditional knowledge and practices of these botanical medicines appears to be diminishing. Considering the need to conserve and document these traditions, the objective of this study was to understand the knowledge, attitudes, and practices of the people who are familiar with botanical medicines, as well as any factors that may influence the perceptions and behaviours associated with the use of medicinal plants. A previously validated survey instrument assessing knowledge, attitudes, and practices on the use medicinal plants was randomly administered to residents of three rural Barbadian communities. The data was analyzed using descriptive statistics and cross tabulations using Chi-squared Tests and Fisher’s Exact Test at a confidence level at 95% and statistical significance at p < 0.05. One hundred and fifty-four participants completed the survey with a response rate of 96%. From participant responses we found that over 75% of the study population used botanical medicines. Key findings included a diverse repertoire of traditional knowledge on the use of medicinal plants, which included a total of 29 medicinal applications cited across 69 different plant species and 39 families. The most popular species among respondents (irrespective of use) were Pimenta racemosa (Mill.) J.W. Moore (FC = 30, RFC = 0.26), Momordica charantia L. (FC = 28, RFC = 0.24), Zingiber officinale Roscoe (FC = 22, RFC = 0.19) and Annona muricata L. (FC = 21, RFC = 0.18). The findings also show the persistence of medico-cultural concepts such as cleansing and cooling remedies, and identified significant associations between the use of botanical medicines and related practices and demographic variables such as education (p = 0.05; Fisher’s Exact Test) and health insurance, χ2 (1, n = 152) = 4.645, p = 0.003. The findings of this study can be used in the identification and archiving of the medicinal plant practices in Barbados and the wider Caribbean, as well as for the larger purpose of biocultural exploration, preservation and further scientific assessment of botanical medicine practices.